Effects of whitening dentifrice on yttria-stabilized tetragonal zirconia polycrystal surfaces after simulating brushing - Pinelli, Lígia Antunes Pereira [UNESP]; Gimenes Olbera, Amanda Caroline [UNESP]; Candido, Lucas Miguel [UNESP]; Miotto, Larissa Natiele [UNESP]; Antonio, Selma Gutierrez [UNESP]; Fais, Laiza Maria Grassi [UNESP] (Elsevier, 2017)
Statement of problem The changes that occur after brushing yttria-stabilized tetragonal zirconia polycrystal (Y-TZP) are unknown. These changes may favor the retention of microorganisms and chemisorption of water, impairing its longevity. Objective The purpose of this in vitro study was to evaluate the effects of a whitening dentifrice on Y-TZP surfaces after simulating 10 years of brushing. Material and methods Seventy-two bar-shaped specimens (20×4×1.2 mm) were divided into 4 groups: storage in distilled water (SW, control), brushing with distilled water (BW), brushing with dentifrice (BD), and brushing with whitening dentifrice (BWD). Brushing was conducted using a linear brushing machine (878 400 cycles, 0.98 N, soft toothbrush). The mean roughness (Ra) was analyzed with a profilometer and the superficial topography with scanning electron microscopy (SEM) at baseline and after treatment. Crystalline phases were characterized using x-ray diffraction. Baseline and posttreatment Ra were analyzed using the 1-way ANOVA and Tukey HSD multiple comparison test; the paired t test was used for intragroup comparison (all α=.05). Results The Ra (μm) means (before/after treatment) were SW 0.28/0.28; BW 0.32/0.31; BD 0.28/0.36; BWD 0.30/0.20. No statistically significant difference was found for Ra at baseline (P=.108) than for posttreatment results (P<.001); the BD group had higher Ra values when compared with baseline (P=.019); the BWD group had the lowest values (P<.001). The BD surfaces showed pronounced scratches and detachment of the surface, while BWD showed smoother surfaces; similar crystallographic results among groups were observed. Conclusions Brushing Y-TZP with conventional dentifrice increased roughness, while brushing with whitening dentifrice reduced roughness. Neither dentifrice changed the crystallographic phases after brushing.